151 Intermediate Dosing of Recombinant Human Bone Morphogenetic Protein-2 Improves Fusion Rates With No Increase in Major Complications but Does Not Improve Health Related Quality of Life for Adult Spinal Deformity at Minimum 2 Years: A Prospective, Multicenter Analysis. Issue Volume 61:Issue CN Supp. 1(2014)Supplement (1st August 2014) - Bess, Shay; Line, Breton G.; Lafage, Virginie; Ames, Christopher P.; Boachie-Adjei, Oheneba; Burton, Douglas C.; Hart, Robert; Gupta, Munish; Klineberg, Eric; Mundis, Gregory; Hostin, Richard A.; Schwab, Frank; et al.
Abstract: INTRODUCTION: Controversy persists regarding Recombinant Human Bone Morphogenetic Protein-2 (rhBMP-2) use in spine surgery. We compared minimum 2 year complications, fusion rates and clinical outcomes for BMP and NOBMP patients in a prospective, multicenter consecutive cohort. METHODS: Multicenter, prospective analysis of complications, spine fusion (Lenke grade) and health related quality of life (health-related quality of life [HRQOL]; SRS-22r, Oswestry Disability Index, SF-36) for consecutive ASD patients receiving rhBMP-2 (BMP) or no BMP (NOBMP). Inclusion criteria: ASD, age = 18 years, spinal fusion = 4 levels, minimum 2 years follow-up. Type and timing of complications were evaluated and multivariate analysis (MARS) performed. BMP was divided into posterolateral dose used; <5, 5 to 10, and >10 mg/level. RESULTS: One hundred ninety-nine patients, with a mean follow up 44.3 months (range, 23.3-60.3), met inclusion criteria. BMP (n = 130; mean posterolateral dose/level 3.1 mg, mean interbody dose/level 1.8 mg) had similar preoperative deformity and total fusion levels as NOBMP (n = 69). BMP had greater Charleson comorbidity index, operative time, and anteroposterior surgery than NOBMP; NOBMP had more 3 column osteotomies than BMP ( P < .05). Early minor complications (<3 and 3-6 months) were greater for BMP vs NOBMP ( P < .05). Total major complications were similar for BMP vs NOBMP; however, NOBMP had greater return to surgery rates at 6 to 12 months, greater pseudarthrosis rates, and deep infection and implant failures constituted a greater proportion of complications for NOBMP vs BMP ( P < .05). BMP had greater interbody and posterior fusion grades and rates than NOBMP ( P < .05). BMP dosed at 5 to 10 mg demonstrated greater fusion grades and rates vs NOBMP, while BMP dosed at <5 mg group did not. HRQOL values were similar for BMP vs NOBMP at all time points. CONCLUSION: RhBMP-2 at intermediate dosing may improve fusion rates with no increase in major complications in ASD surgery; however, HRQOL measures were similar between groups. Longer follow-up is needed to assess if fusion rates correlate with HRQOL and revision surgery.